Dimensional analysis of food processes - Delaplace, Guillaume; Loubiere, Karine, 1975-; Ducept, Fabrice; Jeantet, Romain (Modeling and control of food processes set., 2015)
This book deals with the modeling of food processing using dimensional analysis. When coupled to experiments and to the theory of similarity, dimensional analysis is indeed a generic, powerful and rigorous tool making it possible to understand and model complex processes for design, scale-up and /or optimization purposes. This book presents the theoretical basis of dimensional analysis with a step by step detail of the framework for applying dimensional analysis, with chapters respectively dedicated to the extension of dimensional analysis to changing physical properties and to the use of dimensional analysis as a tool for scaling-up processes. It includes several original examples issued from the research works of the authors in the food engineering field, illustrating the conceptual approaches presented and strengthen the teaching of all. Discusses popular dimensional analysis for knowledge and scaling-up tools with detailed case studies Emphasises the processes dealing with complex materials of a multiphase nature Introduces the concept of chemical or material similarity and a framework for analysis of the functional forms of the property.